Effect of Work Placement and Work Motivation on Achievement at Oti Fried Chicken - Efo Vista Sidupa; Agus Sugiarto (Budapest International Research and Critics University, 2022)
Job placement is a decision to place someone to be placed in a specified position. Motivation is the result of a number of processes that are internal or external to an individual that causes an enthusiastic attitude in carrying out an activity. This study aims to examine the effect of work placement and work motivation on job performance at Oti Fried Chicken. The method used in this study is a quantitative method with multiple linear regression analysis techniques. The population of this study was 30 people and the number of respondents was 30 people, using the saturated sampling method. The results of the study show that work placement and work motivation have an effect on work performance.